Sustainability aspects of energy crops in arid isolated island states: the case of Cyprus. (December 2015) - Fokaides, Paris A.; Tofas, Loizos; Polycarpou, Polycarpos; Kylili, Angeliki
Highlights: This study examines sustainability aspects of energy crops cultivation in an arid insular island state. Implementation of multicriteria techniques justified the most appropriate energy crops. Production costs result to a non-competitive price compared to the commodities prices of the examined grains in the national market. GIS analysis defined the limited possibility of promotion of energy crops in Cyprus. Appropriate indigenous second generation crops with limited irrigation demands were determined as a vital alternative. Abstract: The promotion of policies aiming to the establishment of sustainable energy crops cultivation is currently one of the major efforts in the field of biomass. Stakeholders and experts are struggling to define and adopt those measures which will enable the promotion of appropriate energy crops. This study examines sustainability aspects of energy crops promotion in Cyprus, an island state in the Mediterranean, with arid climate, limited water resources, yet with strict biomass penetration targets arising from the European 2020 policy. The main input in this study is the detailed characterization of the performance of six energy crops in Cyprus. Through a multicriteria analysis, this work prioritizes the suitability of these crops in Cyprus, based on specific quantitative criteria. The sustainability of the most promising energy crops that result from this process are assessed both in terms of the production costs as well as of the potential production yield using Geographical Information System (GIS). According to the outcome of this analysis, it is shown that the possibility of promotion of energy crops in Cyprus is extremely limited and in any case insufficient to satisfy the expected contribution of biofuels in the energy mix of the island. Also the results prove that the production costs result to a non-competitive price compared to the commodities prices of the examined grains in the national market. Based on the findings of this study, strategic guidelines for the development of a framework for the sustainable promotion of energy crops in Cyprus are provided as food for thought.